2011
DOI: 10.1016/j.tox.2011.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Induction of DNA damage in human urothelial cells by the brominated flame retardant 2,2-bis(bromomethyl)-1,3-propanediol: Role of oxidative stress

Abstract: 2, 2-Bis (bromomethyl)-1, 3-propanediol (BMP) is an extensively used brominated flame retardant found in urethane foams and polyester resins. In a two year dietary study conducted by the National Toxicology Program, BMP caused neoplastic lesions at multiple sites including the urinary bladder in both rats and mice. The mechanism of its carcinogenic effect is unknown. In the present study, using SV-40 immortalized human urothelial cells (UROtsa), endpoints associated with BMP induced DNA damage and oxidative st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…Previous studies have shown the involvement of ROS in inducing DNA damage and cell cycle arrest [14], [17]. Therefore, ROS generation was determined using flow cytometer by measuring the fluorescence of DCF, which is formed due to the oxidation of DCFDA by endogenous peroxides.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown the involvement of ROS in inducing DNA damage and cell cycle arrest [14], [17]. Therefore, ROS generation was determined using flow cytometer by measuring the fluorescence of DCF, which is formed due to the oxidation of DCFDA by endogenous peroxides.…”
Section: Resultsmentioning
confidence: 99%
“…This cell line was generated from the normal human bladder epithelium and immortalized with the SV-40 large T antigen (Rossi et al, 2001). Cell culture conditions were as previously described by (Kong et al, 2011; Wnek et al, 2011). …”
Section: Methodsmentioning
confidence: 99%
“…The assay was performed as previously reported by (Kong et al, 2011). Briefly, UROtsa cells (5 × 10 5 cells/ml) and freshly isolated, suspended hepatocytes (5 × 10 5 cells/ml) were incubated with BMP (10–100 µM) at 37 °C for 1 h. All control and treated cultures received the same final concentration of vehicle (0.5% EtOH).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations